Digital Scholarship: Identity, Interdisciplinarity, and Openness - Scanlon, Eileen (Frontiers in Digital Humanities, 2018)
This paper considers the impact of changes in the landscape of scholarly communication on the activities of academics. These changes are considered through the lens of the practices examined by educational technology academics at the Open University who have conducted a number of related research projects under the theme of digital scholarship. This paper reviews the changes to the definition of scholarship and interviews conducted on academic practices conducted as Phase one of these activities (see also Scanlon, 2013). It then comments on the findings of Phase two of the project which investigated the use of social media and the usefulness and visualisation of such activities. The findings are considered in the light of trends towards working practices involving interdisciplinarity and openness.